2008
DOI: 10.1007/s10562-008-9531-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the High Activity and Stability of Co3O4 in Low-temperature CO Oxidation

Abstract: In this paper, the Co 3 O 4 catalysts prepared by the liquid phase precipitation method were investigated with respect to their activity and stability in CO oxidation reaction. The Co 3 O 4 catalysts were comparatively investigated by thermal gravimetry analysis (TG-DTG), X-ray powder diffraction (XRD), N 2 adsorption, CO titration and O 2 -temperature program desorption (O 2 -TPD). The results of XRD show that all the catalysts exist as a pure Co 3 O 4 phase with the spinel structure. The high catalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 35 publications
4
44
0
1
Order By: Relevance
“…Therefore, the influence of pretreatment temperature on mesoporous Co 3 O 4 is dramatic. In the literature, some researchers found that pure Co 3 O 4 is active for CO oxidation below ambient temperature [13,24], whereas others observed activities only at higher temperatures [36]. Even the recent paper reporting high catalytic activity for mesoporous Co 3 O 4 also described its instability.…”
Section: Catalytic Co Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the influence of pretreatment temperature on mesoporous Co 3 O 4 is dramatic. In the literature, some researchers found that pure Co 3 O 4 is active for CO oxidation below ambient temperature [13,24], whereas others observed activities only at higher temperatures [36]. Even the recent paper reporting high catalytic activity for mesoporous Co 3 O 4 also described its instability.…”
Section: Catalytic Co Oxidationmentioning
confidence: 99%
“…The pioneering work of Haruta and coworkers demonstrated excellent CO oxidation catalysed by finely dispersed gold nanoparticles [12]. However, because of the high cost of noble metals, cheaper metal oxide catalysts are being actively sought [13][14][15][16][17][18][19][20][21][22][23][24]. Despite the high internal surface area of mesoporous transitional metal oxides, the redox activity of their surfaces and the confinement of reactions close to the surface due to the dimensions of the pores, investigation of ordered mesoporous metal oxides as CO oxidation catalysts has been limited to that of only a few isolated systems, e.g., CuO/meso-CeO 2 [25], Pt/meso-Ce 0.5 Zr 0.5 O 2 [26], and mesoporous Co 3 O 4 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt oxide catalysts show high activity for CO-PROX in H 2 -rich gases and for low-temperature CO oxidation [7][8][9][10][11][12][13][14][15]. We found that Co 3 O 4 -CeO 2 and Co 3 O 4 -CeO 2 -MnO x catalysts exhibited good catalytic performance for CO-PROX in H 2 -rich gases and could completely remove CO from H 2 -rich gases at ∼170 • C [8,9].…”
Section: Introductionmentioning
confidence: 77%
“…Within the first 24 h, the relatively smooth surfaces turned into zigzag periodic and rough nanowires, the pore volume dropped by~46%, and the Brunauer-Emmett-Teller (BET) surface area decreased from 8 m 2 /g to 4 m 2 /g. Compared to the surface area decrease in conventional powder-type catalysts, ZnO, TiO 2 , and Co 3 O 4 nano-array catalysts showed much higher thermal stability [33][34][35].…”
Section: Stability Propertiesmentioning
confidence: 93%